Faktor-faktor yang mempengaruhi kualitas hidup lansia - Nugrahadi Dwi Pasca Budiono; Adbur Rivai (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
The health of the elderly, which decreases with age, will affect the quality of life of the elderly. Increasing age will be accompanied by decreased body function, the onset of various diseases, body balance and the risk of falling. This study aims to determine the factors that affect the quality of life of the elderly in Surabaya, East Java, by applying the HRQoL questionare. This study is survey research, which was conducted on 94 older people aged over 60 years. Multiple regression analysis was conducted to analyze factors related to the quality of life of the elderly, including predisposing factors, support, health needs and behaviour. The results showed that the need factor, namely health status, most significantly affects the quality of life of the elderly. The findings of this study can be used to develop intervention policies to improve the quality of life of the elderly